Practical Aspects of the Implementation of International Financial Reporting Standards and Accounting Policies in Business Structures - Shot Anna P.; Honcharuk Svitlana M.; Priymak Svitlana V. (Problemi Ekonomiki, 2020)
Ukraine’s membership in the European Union envisages the introduction of and compliance with the requirements and norms of European law, accompanied by reforms in almost all sectors of the Ukrainian economy including accounting. The main objective of the accounting reform is to bring the national accounting system in line with the requirements of the market economy and international accounting and reporting standards. The aim of the article is to study practical aspects of implementing International Financial Reporting Standards (IFRS) and accounting policies in business structures, with regard to national accounting features, in order to assess their impact on the performance. The article considers advantages of domestic enterprises in preparing reports in accordance with International Financial Reporting Standards, reveals problems associated with the application of the principles and requirements of IFRS, and describes the specifics of the transition of domestic enterprises to IFRS with regard to national peculiarities. The practical aspects of the implementation of IFRS and the principles of accounting policies in business structures are studied, taking into consideration national accounting features, in order to assess their impact on business entities’ performance. The influence of the transition to tax obligations and tax consequences for enterprises in reporting under international standards is calculated. Based on the results of the study, it is concluded that the transformational differences at the stage of transition to IFRS become neutral before taxation; business owners, investors and lenders receive high-quality financial statements to make informed and sound management decisions.